Calpain mediates epithelial cell microvillar effacement by enterohemorrhagic Escherichia coli - YuShuan eLai; Kathleen eRiley; Andrew eCai; Andrew eCai; John M Leong; Ira M. Herman (Frontiers in Microbiology, 2011)
A member of the attaching and effacing (AE) family of pathogens, enterohemorrhagic Escherichia coli (EHEC) induces dramatic changes to the intestinal cell cytoskeleton, including effacement of microvilli. Effacement by the related pathogen enteropathogenic E. coli (EPEC) requires the activity of the Ca+2-dependent host protease, calpain, which participates in a variety of cellular processes, including cell adhesion and motility. We found that EHEC infection results in an increase in epithelial (CaCo-2a) cell calpain activity and that EHEC-induced microvillar effacement was blocked by ectopic expression of calpastatin, an endogenous calpain inhibitor, or by pretreatment of intestinal cells with a cell-penetrating version of calpastatin. In addition, ezrin, a known calpain substrate that links the plasma membrane to axial actin filaments in microvilli, was cleaved in a calpain-dependent manner during EHEC infection and lost from its normal locale within microvilli. Calpain may be a central conduit through which EHEC and other AE pathogens induce enterocyte cytoskeletal remodeling and exert their pathogenic effects.